Perceptions of Frontline Staff to Training and Communication Tools to Support Adults with Intellectual Disabilities to Report Abuse and Neglect: "Something to Work with". Issue 1 (2nd January 2020) - Johnson, Hilary; Yee, Ruby
Abstract: Adults with intellectual and communication disabilities are more vulnerable than the general population to becoming victims of abuse and neglect. Approaches to giving a voice to this population remain scarcely researched, while current literature highlights the need for frontline disability workers to receive training and communication resources in abuse and neglect. This study explored the perceptions of frontline staff to using a safeguard toolkit consisting of resources to raise staff awareness and communication aids to assist with client disclosure of abuse and neglect, after receiving one day of training. Qualitative methods were followed, with data collected through telephone interviews. Three themes that emerged were appreciation, uncertainty and improvements. Although the tools were received enthusiastically and participants reported a raised awareness of abuse and neglect, the tools had not been used to facilitate disclosures of abuse, even when abuse had been suspected. Although the face-to face training raised awareness about abuse and neglect of individuals communication disabilities, the staff remained uncertain of how to the use the tools or for whom they were applicable. Participants requested increased support to use the tools confidently. Alternative models of training and support may be required in order for frontline workers to be confident at supporting individuals with intellectual and communication disabilities to speak out about abuse and neglect.